(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Mental health is now an important social issue in India, but most people still do not talk about it openly. Many people think that mental health problems mean a person is weak, that it brings shame to the family, or that the person is behaving in a strange way. They do not understand that these are real emotional and psychological problems, just like physical health problems. In this situation, films play a big role because they affect the way people think and feel. Bollywood is one of the most popular forms of entertainment in India, and it has the power to change how people think about sensitive topics like mental health. This research paper looks at three Bollywood films — Dear Zindagi (2016), Taare Zameen Par (2007), and Karthik Calling Karthik (2010) — to understand how Indian cinema shows mental health problems and what kind of solutions these films suggest to society. These three films were chosen because each one shows mental health in a different situation. Dear Zindagi is about a young woman living in a city who deals with anxiety, emotional pain, and goes to therapy. Taare Zameen Par is about a child who has dyslexia, suffers emotionally, and faces a lot of pressure from the education system. Karthik Calling Karthik is about a man working in a city who feels very lonely, has low self-confidence, carries past trauma, and eventually goes through a mental breakdown. The paper says that these films do not just show mental health as a problem. They also help people become more aware, feel empathy, and learn about mental health in a social way. These films help viewers understand that having a mental health problem does not mean a person is "mad" or weak. It simply means they are going through a human experience that needs support, understanding, and proper care. At the same time, the paper also points out that films have some limits. Sometimes movies make complicated mental health conditions look too simple, or they solve big problems too quickly and dramatically. But even with these drawbacks, such films are still important because they start conversations and help reduce the shame or fear people feel around mental health. This study looks closely at a few selected films using a qualitative and thematic approach, meaning it focuses on ideas, themes, and meaning rather than numbers or data. The study finally concludes that Bollywood has the power to change how people in India think about mental health. It can do this by encouraging open conversations, making therapy feel normal, helping people understand their emotions better, and building a kinder and more caring society.